Immediate X delayed loading dental implants: An overview - Perez, Luciano Elias da Cruz (2007)
The aim of this investigation was to accomplish an overview about the principles of the indication and of the success parameters involving immediate and delayed loading dental implants procedures. Studies about the philosophies (immediate and delayed loading dental implants) and their clinical indications will be discussed in order to overview the rules for the clinical success in both techniques. In addition, studies regarding the criteria for immediate loading implants as primary stabilization, surface treatments and bone density and amount will be also analyzed. More important than the philosophy selection, is how and when to use it according to biomechanical rules and principles. Among the vast limitations pointed by the literature regarding procedures of immediate and delayed loading are evidenced the parafunctional habits, primary stabilization, bone quality, surface treatments and the number of dental implants. The anterior region of the jaw seems to be associated with a major percentage of satisfactory results, regardless of rehabilitation procedures. Although several studies have demonstrated high success rates for the immediate loading dental implants, several aspects remain without an explicit definition and further studies are needed to elucidate some reservations.